Providing Students with Flexible and Adaptive Learning Opportunities using Lecture Recordings - Larian M Nkomo; Ben K Daniel (Flexible Learning Association of New Zealand, 2021)
Lecture recordings are widely used within higher education as a means of engaging and enriching students learning, by providing more adaptable, highly flexible and convenient access to learning materials. However, educators have increasingly raised concerns that lecture recording availability contributes to a decline in students attending lectures. This study explores how students engage with lecture recordings and the extent to which they perceive access to these resources contributes to their learning. We administered self-reported measures (questionnaire) to undergraduate and postgraduate students (n=664) who had access to lecture recordings. The quantitative data were summarised using descriptive statistics. We then applied a sentiment analysis technique to triangulate and contest the results derived from the quantitative analysis. Overall, the results in this study indicate that lecture recordings can provide students with flexibility and convenient access to learning materials, and ultimately enhancing their learning experience. Most respondents regarded lecture recording as supplementary learning resources not a replacement for lectures; stating that the availability of lecture recordings did not influence their decisions to attend lectures. Respondents reported that they used lecture recordings to prepare for exams, revise and compare their notes taken in class.